English Education Student's Perception And Motivation in Learning Descriptive Writing Skills Through Instagram - Sophia Syachsalsabillah; Ade Ismail Ramadhan Hamid (English Language Education Department, Universitas Majalengka, 2024)
Recently, the use of Instagram in education garnered significant interest due to its visual popularity among students. The potential of Instagram to facilitate communication, collaboration, and creative expression made it valuable asset in modern educational strategies. This study investigates students' perceptions and motivations in learning descriptive writing skills through Instagram. The participants of this study were 33 second-semester English Education students from University of Muhammadiyah Kalimantan Timur, using mixed-method approach: Data were collected through closed-ended questionnaires via Google Forms and analyzed using descriptive statistic SPSS, and qualitative data were gathered through open-ended interview semi-structured with 5 selected students convenience sampling method. The results of this study indicate that students have a very positive view of using Instagram for learning writing skills and that it motivates them in writing. Additionally, Instagram's interactive features, such as comments and direct messages, allow for quick and constructive feedback, further increase students' motivation and writing skills.